Electrode foil, preparation method thereof and aluminum electrolytic capacitor

By forming a double-layer composite oxide film of Al2O3 and SiO2 on the electrode foil of the aluminum electrolytic capacitor, the shortcomings of the electrode foil in terms of hydration resistance, corrosion resistance and specific capacity are solved, and higher frequency stability and longer service life are achieved.

CN119650305APending Publication Date: 2025-03-18DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411560311.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The electrode foils of existing aluminum electrolytic capacitors have shortcomings in hydration resistance, corrosion resistance and specific capacitance, and are difficult to meet the requirements of high frequency, low impedance and long life.

Method used

By melting the corrosion foil into a treatment, an Al2O3 film is formed, and then a nanoporous SiO2 film is formed on its surface, and a phosphating treatment and annealing treatment are performed to form a double-layer composite oxide film of the inner layer of Al2O3 and outer layer of SiO2.

Benefits of technology

It significantly improves the specific capacitance, hydration resistance and corrosion resistance of the electrode foil, extends the service life of the capacitor, and reduces leakage current.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650305A_ABST
    Figure CN119650305A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to an electrode foil, a preparation method thereof and an aluminum electrolytic capacitor, and the preparation method of the electrode foil comprises the steps: carrying out the formation of a corrosion foil, and forming an aluminum oxide film on the surface of the corrosion foil; forming a nano-porous silicon dioxide film on the surface of the aluminum oxide film to obtain an electrode foil with an aluminum oxide-silicon dioxide double-layer composite oxide film; and sequentially carrying out phosphating treatment and annealing treatment on the electrode foil. According to the preparation method, after the corrosion foil is subjected to formation treatment to form the Al2O3 film, the nano-porous SiO2 film is formed on the surface of the Al2O3 film, the SiO2 film is subjected to phosphating treatment to contain phosphorus elements, the phosphorus elements are uniformly diffused into the SiO2 film, a double-layer composite oxidation film with the Al2O3 inner layer and the SiO2 outer layer is obtained, and the specific volume, the hydration resistance and the corrosion resistance of the low-voltage electrode foil are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to an electrode foil and a preparation method thereof and an aluminum electrolytic capacitor. Background Art

[0002] Aluminum electrolytic capacitors have the characteristics of large capacitance per unit volume, small size, and low cost. They are widely used in tuning, filtering, bypassing, coupling, energy storage, etc. With the development of science and technology, the assembly density and integration of electronic equipment have further increased, and higher requirements have been put forward for aluminum electrolytic capacitors: small size, large capacity, long life, high frequency and low impedance. As a key component of aluminum electrolytic capacitors, the performance of aluminum electrode foil has become one of the key factors restricting the service life and reliability of aluminum electrolytic capacitors.

[0003] The volume of low-voltage aluminum electrolytic capacitors is mainly restricted by the capacity of the electrode foil, and the quality of the electrode foil's hydration resistance, corrosion resistance and other properties also directly affects the electrical performance of the capacitor. Therefore, how to further improve the specific capacity, hydration resistance and corrosion resistance of the electrode foil for aluminum electrolytic capacitors is a technical problem that the industry urgently needs to solve. Summary of the invention

[0004] The main purpose of the present invention is to provide an electrode foil and its preparation method and an aluminum electrolytic capacitor. The preparation method of the present invention is to form an Al2O3 film by chemical treatment of the corroded foil, and then form a nanoporous SiO2 film on the surface of the Al2O3 film. The SiO2 film contains phosphorus after phosphating treatment. The phosphorus element is uniformly diffused into the SiO2 film to obtain a double-layer composite oxide film of inner Al2O3 and outer SiO2, thereby improving the specific capacity, hydration resistance and corrosion resistance of the low-voltage electrode foil.

[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0006] In a first aspect, the present invention provides a method for preparing an electrode foil, which comprises the following steps: subjecting a corroded foil to a chemical treatment to form an aluminum oxide film on its surface; forming a nanoporous silicon dioxide film on the surface of the aluminum oxide film to obtain an electrode foil having an aluminum oxide-silicon dioxide double-layer composite oxide film; and subjecting the electrode foil to a phosphating treatment and an annealing treatment in sequence.

[0007] In some embodiments of the present invention, the silicon dioxide film has a thickness of 2 nm to 25 nm.

[0008] In some embodiments of the present invention, the silicon dioxide film is formed by one or more methods selected from chemical vapor deposition, physical vapor deposition, plasma enhanced chemical vapor deposition and atomic layer deposition.

[0009] In some embodiments of the present invention, the deposition reaction gases are SiH4 and N2O, and the flow ratio of SiH4 to N2O is 1:1 to 1:6.

[0010] In some embodiments of the present invention, the phosphating treatment uses a phosphorus-containing solution.

[0011] In some embodiments of the present invention, the mass percentage of phosphorus in the phosphorus-containing solution is 0.08% to 15%.

[0012] In some embodiments of the present invention, the phosphorus-containing solution comprises one or more of inorganic phosphoric acid, inorganic phosphate, organic phosphoric acid and organic phosphate.

[0013] In some embodiments of the present invention, the inorganic phosphoric acid is one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid and hypophosphorous acid.

[0014] In some embodiments of the present invention, the inorganic phosphate is one or more of orthophosphate, pyrophosphate, tripolyphosphate, metaphosphate, hypophosphate, phosphite, pyrophosphite, metaphosphite and hypophosphite.

[0015] In some embodiments of the present invention, the organic phosphoric acid is one or more of trimethylphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and acetylphosphonic acid.

[0016] In some embodiments of the present invention, the organic phosphate is one or more of trimethylphosphonate, aminotri(methylene)phosphonate, ethylenediaminetetra(methylene)phosphonate, diethylenetriaminepenta(methylene)phosphonate, and acetyl phosphate.

[0017] In some embodiments of the present invention, the phosphorus element in the phosphorus-containing solution exists in the form of one or more phosphate ions selected from monohydrogen phosphate, dihydrogen phosphate, and orthophosphate.

[0018] In some embodiments of the present invention, the temperature of the phosphating treatment is 40°C to 85°C.

[0019] In some embodiments of the present invention, the phosphating treatment time is 0.5 min to 15 min.

[0020] In some embodiments of the present invention, the annealing treatment is performed at a temperature of 120°C to 350°C.

[0021] In some embodiments of the present invention, the annealing treatment time is 1 min to 20 min.

[0022] In some embodiments of the present invention, the chemical formation treatment includes one to six stages of chemical formation, and the chemical formation liquid used in each stage of chemical formation is independently selected from one or more of ammonium adipate solution, boric acid solution and diammonium dihydrogen phosphate solution.

[0023] In some embodiments of the present invention, the formation temperature of each stage of formation is independently 65° C. to 90° C., and the formation time of each stage of formation is independently 2 min to 20 min.

[0024] In some embodiments of the present invention, the current density of each stage is independently 10 mA / cm 2 ~100mA / cm 2 .

[0025] In some embodiments of the present invention, in each stage of formation, the formation voltage increases step by step from the first stage to the last stage.

[0026] In some embodiments of the present invention, the mass percentage of the formation liquid used in each stage of formation is independently 0.3% to 20%.

[0027] In some embodiments of the present invention, the preparation method further comprises performing at least one depolarization treatment after the chemical formation treatment and before forming the nanoporous silica film.

[0028] In some embodiments of the present invention, the depolarization treatment is selected from one or more of a heat treatment method and a phosphoric acid method.

[0029] In some embodiments of the present invention, the temperature of the heat treatment method is 400° C. to 550° C., and the time of the heat treatment method is 1 min to 15 min.

[0030] In some embodiments of the present invention, the temperature of the phosphoric acid method is 40° C. to 90° C., and the time of the phosphoric acid method is 0.5 min to 15 min.

[0031] In some embodiments of the present invention, the solution used in the phosphoric acid method contains inorganic phosphoric acid and / or organic phosphoric acid.

[0032] In some embodiments of the present invention, the inorganic phosphoric acid used in the phosphoric acid method is selected from one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid and hypophosphorous acid.

[0033] In some embodiments of the present invention, the organic phosphoric acid used in the phosphoric acid method is selected from one or more of trimethylphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and acetylphosphonic acid.

[0034] In some embodiments of the present invention, the mass percentage of phosphorus in the solution used in the phosphoric acid method is 0.2% to 15%.

[0035] In some embodiments of the present invention, the preparation method further comprises performing at least one supplementary formation after the depolarization treatment and before forming the nanoporous silica film.

[0036] In some embodiments of the present invention, the temperature of the patch formation is 65° C. to 90° C., and the time of the patch formation is 2 min to 20 min.

[0037] In some embodiments of the present invention, the current density of the patch formation is 10 mA / cm 2 ~100mA / cm 2 .

[0038] In some embodiments of the present invention, the voltage of the complementary formation is 90% to 100% of the highest formation voltage of the formation treatment.

[0039] In some embodiments of the present invention, the treatment solution used in the patch formation is selected from one or more of ammonium adipate solution, boric acid solution and diammonium dihydrogen phosphate solution.

[0040] In some embodiments of the present invention, the mass percentage of the solute in the treatment solution used for the replenishment formation is 0.3% to 20%.

[0041] In some embodiments of the present invention, the method for preparing the electrode foil includes: subjecting the corrosion foil to a chemical treatment to form an aluminum oxide film on its surface; subjecting the chemical foil obtained after the chemical treatment to at least one depolarization treatment and re-forming; forming a nanoporous silicon dioxide film on the surface of the aluminum oxide film to obtain an electrode foil having an aluminum oxide-silicon dioxide double-layer composite oxide film; and subjecting the electrode foil to a phosphating treatment and an annealing treatment in sequence.

[0042] A second aspect of the present invention provides an electrode foil, which is prepared by the preparation method described in the first aspect of the present invention.

[0043] According to a third aspect of the present invention, an aluminum electrolytic capacitor is provided. The aluminum electrolytic capacitor comprises an electrode foil prepared by the preparation method according to the first aspect or the electrode foil according to the second aspect.

[0044] Compared with the prior art, the present invention achieves the following technical effects:

[0045] 1. The specific volume of the electrode foil prepared by the present invention increases. The relative dielectric constant εr of SiO2 is 3.9, and its formation constant K is 0.39 nm / V. The relative dielectric constant εr of Al2O3 is 9, and its formation constant K is 1.3 nm / V. The εr / K of the SiO2 film is greater than the εr / K of the Al2O3 film, so the specific volume of the electrode foil is increased.

[0046] 2. The electrode foil prepared by the present invention has enhanced hydration resistance, and SiO2 is deposited to produce Si-OH. Phosphate can easily diffuse in the nanoporous SiO2 film and adhere to the surface of SiO2 particles. Phosphate will combine with silicon hydroxyl groups and connect to the surface of SiO2 particles, forming a hydration-resistant layer similar to phosphorus silicon glass in the outermost layer of the composite oxide film. At the same time, an efficient water-retaining layer with a complex three-dimensional network structure containing silicon, phosphorus and aluminum elements is formed at the interface between the SiO2 film and the Al2O3 film, which inhibits the Al atoms on the surface of the aluminum oxide film from combining with water to form AlO-H bonds and Al-OH bonds, greatly reduces the adsorption degree of water molecules on the surface, and inhibits the diffusion of water molecules to the inner layer of the oxide film, thereby eliminating surface active points and improving the hydration resistance of the electrode foil.

[0047] 3. The corrosion resistance of the electrode foil prepared by the present invention is enhanced. The SiO2 film is an acidic oxide film and is not easy to react with an acidic electrolyte. This improves the ability of the internal anode foil to resist electrolyte corrosion during the preparation and use of the capacitor, thereby extending the service life of the capacitor.

[0048] 4. The preparation process of the electrode foil in the present invention is simple and compatible with the existing process. The SiO2 film is deposited on the Al2O3 surface only after the chemical formation process is completed, and the growth rate and thickness of the SiO2 film can be accurately controlled without affecting the chemical formation process in the previous stage. If the SiO2 film is grown before or during the chemical formation, excessive silicon elements diffuse into the oxide film layer, which will inhibit the transformation of crystalline aluminum oxide, thereby reducing the withstand voltage value of the oxide film. In addition, during the phosphating process after the SiO2 film is deposited, the phosphorus element mainly stays in the SiO2 layer and is not easy to enter the inner side of the aluminum oxide film, only on the surface of the oxide film, so it has little effect on other properties of the aluminum oxide film.

[0049] 5. The withstand voltage value of the electrode foil prepared by the present invention is improved. The SiO2 film has high insulation, high hardness and good wear resistance, which can enhance the insulation performance of the oxide film. At the same time, the addition of some silicon elements reduces the defects in the Al2O3 film, and the withstand voltage characteristics of the composite oxide film are enhanced.

[0050] 6. The leakage current of the electrode foil prepared by the present invention is reduced. The SiO2-Al2O3 double-layer composite oxide film dielectric layer with better density can effectively reduce the leakage current. When trace silicon and phosphorus elements diffuse into the aluminum oxide film, the defects of the oxide film can be reduced. For example, the diffusion of silicon elements reduces the vacancies in the oxide film, so the leakage current of the electrode foil is reduced.

[0051] 7. The electrode foil prepared by the present invention forms an Al2O3 film first and then forms a nanoporous SiO2 film. The deposition reaction gas can easily diffuse into the sponge-like holes of the Al2O3 film and deposit, and finally forms a SiO2-Al2O3 double-layer composite oxide film. The SiO2 film is not formed by the adhesion of a nano-colloidal SiO2 solution. SiO2 particles will not agglomerate to block the original hole structure of the corrosion foil and cause a decrease in capacity. There is no need to repeatedly immerse in a colloidal solution containing SiO2 particles and repeatedly heat the foil. The present invention is conducive to reducing costs.

[0052] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0054] Figure 1 Schematic cross-sectional view of an aluminum oxide-silicon dioxide double-layer composite oxide film according to some embodiments of the present invention. DETAILED DESCRIPTION

[0055] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0057] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0058] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0059] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0060] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0061] Although there are literature reports that before or during the formation of high-voltage electrode foil, the sol-gel method is used to successfully prepare SiO2-Al2O3 composite oxide film by impregnating silica sol or its precursor with a certain heat treatment process to improve the specific capacity of the anode foil. However, this method has the following problems:

[0062] (1) The amount of SiO2 adsorbed on the surface of the oxide film is very limited. It is only physically adsorbed on the surface of the oxide film. It is necessary to repeatedly immerse and heat treat to increase the amount of SiO2 adhesion, making the film forming process complicated and cumbersome.

[0063] (2) Additional reagents are needed to enhance the dispersibility of the colloid. The preparation of a highly stable sol solution is complicated. When used, the concentration of the solution containing SiO2 shifts due to the volatilization of the solvent, and the amount of SiO2 attached cannot be accurately controlled, which in turn affects the film quality.

[0064] (3) In the subsequent chemical formation process, the surface SiO2 particles will fall off the surface of the aluminum foil and dissolve in the chemical formation solution. The generated oxide film contains a certain amount of water, and the uniformity of the prepared film is poor; or other components of the colloidal solution affect the stability of the chemical formation process.

[0065] (4) SiO2-Al2O3 composite oxide film SiO2 and Al2O3 are integrated. Excess silicon entering the Al2O3 layer will inhibit the transformation of the amorphous oxide film into the crystalline γ'-Al2O3 with a high dielectric constant during the formation process, resulting in a decrease in specific capacitance.

[0066] (5) Nano-SiO2 particles tend to aggregate and adsorb on the pore walls, blocking the pores and causing a decrease in specific volume. Therefore, the size and dispersibility of nano-SiO2 particles need to be strictly controlled.

[0067] For low-pressure foil, since the pore size of the sponge-like pores on its surface is much smaller than that of high-pressure foil, if the spherical silica agglomerates, it is easy to block the sponge-like pores, resulting in a decrease in specific volume. Therefore, this method is not suitable for low-pressure foil.

[0068] At the same time, in order to further improve the hydration resistance of the electrode foil, the generation of oxide film defects must be reduced. The defects of the electrode foil oxide film are mainly impurity defects, loose hydrated oxide layer on the outermost layer of the oxide film, cracks, etc. The countermeasures to overcome the problems of hydrated porous hydroxides and cracks are to use "depolarization" treatment, use some means to force the closed mouth of the defective part to open, and then fill it up several times to fill the oxide. The main methods include:

[0069] (1) Heat treatment method: heat treat the aluminum anode foil to be formed to open the cracks in the oxide film, and then continue to repair the cracks to better repair the cracks and transform the hydrated oxide into a crystalline oxide.

[0070] (2) Repeatedly cut off the power supply and restore it (voltage change method). When the formation of the anodized film is about to end, the forming voltage is adjusted back to zero. At this time, the oxygen blocked in the cracks is released, making the cracks fully exposed. Continue to apply power to repair, so that an oxide film layer grows at the cracks, making the entire oxide film structure dense and intact.

[0071] (3) Hot water treatment method: the aluminum foil to be formed is passed through a hot water tank to open the closed parts of the oxide film cracks, and then continue to form it to obtain an oxide film with fewer defects.

[0072] (4) Hydrated oxide removal method: the electrode foil is placed in a hydration-resistant reagent such as phosphoric acid (salt), silicate (salt), citric acid (salt) and other solutions for electrical treatment, or immersed and then heat treated, which not only removes the hydrated oxide on the surface of the oxide film but also improves the hydration resistance. The P-OH bond of the phosphate group in the conventional phosphoric acid (salt) hydration-resistant reagent reacts with alumina to form a PO-Al bond, inhibiting the water molecules adsorbed on the surface from forming AlO-H bonds and Al-OH bonds with the surface Al atoms, thereby preventing the adsorption of water molecules on the surface of alumina and improving the hydration resistance of the alumina surface. In order to improve the hydration resistance, it is usually necessary to increase the intensity of phosphoric acid treatment, such as increasing the treatment temperature and extending the treatment time, but this may corrode the inner crystalline aluminum oxide film, and excessive phosphorus entering the aluminum oxide film layer will inhibit the crystal transformation of aluminum oxide, resulting in a decrease in specific volume. At the same time, the higher phosphorus content in the chemical solution is prone to cause environmental pollution and also increases the cost of wastewater treatment.

[0073] In addition, in the internal structure of the capacitor, the conductive electrolyte is in contact with the oxide film. For liquid capacitors, the electrolyte is a neutral to slightly acidic liquid, which is easy to corrode the aluminum oxide film during use. The dielectric material of traditional solid capacitors is to directly impregnate the core package with a conductive polymer, or to impregnate the core package with a monomer or an oxidant to form a conductive polymer through a polymerization reaction. After the conductive polymer is formed, during use, as the capacitor is charged and discharged, the dopant dedoped from the conductive polymer and the acid decomposed by the dopant (such as sulfuric acid produced by p-toluenesulfonic acid) will corrode the aluminum oxide film, deteriorate the performance of the oxide film, cause the capacitor to fail, and greatly shorten the service life of the capacitor. Therefore, it is necessary to enhance the corrosion resistance of the electrode foil to the electrolyte material.

[0074] Therefore, how to further improve the specific volume, hydration resistance and corrosion resistance of low-pressure foil is a technical problem that the industry urgently needs to solve.

[0075] In order to improve the electrostatic capacitance, hydration resistance and corrosion resistance of low-voltage electrode foil, the present invention provides a method for preparing electrode foil for low-voltage aluminum electrolytic capacitors, the preparation method comprising subjecting the corrosion foil to chemical treatment to form an aluminum oxide film on its surface; forming a nanoporous silicon dioxide film on the surface of the aluminum oxide film to obtain an electrode foil having an aluminum oxide-silicon dioxide double-layer composite oxide film; and sequentially subjecting the electrode foil to phosphating treatment and annealing treatment.

[0076] The preparation method of the present invention first forms an Al2O3 film on the anode aluminum foil, and then deposits a SiO2 film to form a double-layer composite oxide film with an inner Al2O3 layer and an outer SiO2 layer, thereby improving the specific volume of the oxide film; the double-layer composite oxide film forms a high-efficiency water-retaining layer, thereby enhancing the hydration resistance of the low-voltage electrode foil; and the SiO2 film is an acidic oxide film, which is not easy to react with acidic substances, while Al2O3 is an amphoteric oxide, which can react with both acidic substances and alkaline substances. Therefore, after the SiO2 film is deposited on the surface of the aluminum oxide, it can be ensured that the anode foil of the liquid capacitor is not easy to corrode in the acidic electrolyte, or the anode foil of the solid capacitor is less affected by the acidic impregnation liquid during the preparation process, thereby enhancing the corrosion resistance of the low-voltage foil during use and extending the service life of the capacitor.

[0077] Chemical treatment

[0078] In the present invention, the etching foil is placed in a chemical forming solution for chemical forming treatment to form an aluminum oxide (Al2O3) film on the surface of the etching foil.

[0079] In some embodiments of the present invention, the chemical treatment includes multi-stage chemical treatment. Generally speaking, the more chemical treatment stages there are, the better the quality control is. However, in view of the actual situation, the chemical treatment in the embodiments of the present invention adopts one to six stages of chemical treatment, for example, one stage chemical treatment, two stage chemical treatment, three stage chemical treatment, four stage chemical treatment, five stage chemical treatment or six stage chemical treatment can be performed. Specifically, the etching foil is placed in a chemical treatment liquid for one to six stages of chemical treatment to form an aluminum oxide (Al2O3) film on the surface of the etching foil.

[0080] In some embodiments of the present invention, the chemical forming liquid used in each stage of chemical forming may be, but not limited to, ammonium adipate, boric acid solution, ammonium dihydrogen phosphate solution, etc., and other commonly used reagents in the prior art may be selected and used according to actual conditions.

[0081] In some embodiments of the present invention, the mass percentage of the chemical liquid used in each stage of chemical formation is independently 0.3% to 20%. Thus, an aluminum oxide film is formed on the surface of the corroded foil. The mass percentage of the chemical liquid used in each stage of chemical formation provided by the present invention can be independently a value of an interval composed of any two values ​​in the above interval, such as 0.3% to 5%, 5% to 10%, 10% to 20%, and so on. The mass percentage of the chemical liquid used in each stage of chemical formation provided by the present invention can also be independently 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value that meets the above range value.

[0082] In some embodiments of the present invention, the corroded foil is placed in a 10% to 20% by mass ammonium adipate solution for one to six stages of chemical formation.

[0083] In some embodiments of the present invention, the formation temperature of each stage of formation is independently 65°C to 90°C, thereby forming an aluminum oxide film on the surface of the corrosion foil. The formation temperatures provided by the present invention can be independently a value of an interval consisting of any two values ​​in the above range, such as 65°C to 80°C, or 80°C to 90°C, and so on. The formation temperatures provided by the present invention can also be independently one of 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any value that meets the above range.

[0084] In some embodiments of the present invention, the formation time of each level of formation is 2min~20min independently of one another, that is, the formation time of each level of formation is 2min~20min independently of one another for the constant time after reaching the set voltage. The formation time provided by the present invention can be the value of the interval composed of any two values ​​in the above-mentioned interval independently of one another, such as can be 2min~10min, can also be 10min~20min, and so on. The formation time provided by the present invention can also be 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, one of 20min or any numerical value that meets the above-mentioned range value independently.

[0085] In some embodiments of the present invention, the current density of each stage is independently 10 mA / cm 2 ~100mA / cm 2 The current density provided by the present invention can be independently a value in the interval consisting of any two values ​​in the above interval, for example, it can be 10mA / cm 2 ~50mA / cm 2 , or 50mA / cm 2 ~100mA / cm 2 , and so on. The current density provided by the present invention can also be 10mA / cm 2 , 20mA / cm 2 、30mA / cm 2 , 40mA / cm 2 , 50mA / cm 2 、60mA / cm 2 , 70mA / cm 2 、80mA / cm 2 、90mA / cm 2 , 100mA / cm 2 or any value that satisfies the above range.

[0086] In the embodiment of the present invention, for the formation voltage of multi-stage formation, generally, from the first stage to the last stage, the formation voltage increases step by step, and the highest formation voltage is set according to the requirements of the specific product, so in actual production, the highest voltage is basically determined, for example, if the production product requires an electrode foil of 21V, its highest formation voltage can be set to 21V~22V; for another example, if the production product requires an electrode foil of 115V, its highest formation voltage can be set to 115V~117V. Therefore, the formation voltage of each stage of formation can be set according to the specific highest formation voltage without specific limitation.

[0087] In some embodiments of the present invention, in a multi-stage formation, the formation voltage increases step by step from the first stage to the last stage. For example, for a five-stage formation, the formation voltages from the first stage to the fifth stage are 20±3%, 40±3%, 60±3%, 80±3%, and 100% of the highest formation voltage, respectively.

[0088] It is worth mentioning that for low-voltage electrode foil, the forming liquid, the mass percentage of the forming liquid, the forming temperature, the forming time, the current density, etc. of each stage of formation may be the same or different. Usually, for the convenience of control, the forming liquid and its mass percentage, the forming temperature, the forming time, the current density, etc. used in each stage of formation are the same. Of course, in order to enhance certain characteristics, the forming liquid of a certain stage of formation may be different (such as adding a small amount of other reagents or components), and the temperature may also be different (for example, the temperature of one stage is set to 85°C, and the temperature of the rest is 75°C). It needs to be set in combination with actual requirements and is not specifically limited.

[0089] Depolarization treatment

[0090] The purpose of the depolarization treatment in the present invention is to overcome the cracking problem of hydrated oxides and oxide films. The depolarization treatment mainly uses means to force the closed part of the defective part to open, and then fill the defect after the repair is formed.

[0091] In the embodiment of the present invention, the depolarization process may be repeated multiple times according to actual needs.

[0092] In an embodiment of the present invention, the depolarization treatment is selected from but not limited to at least one of a heat treatment method and a phosphoric acid method. For example, the heat treatment method and the phosphoric acid method are mainly used for the depolarization treatment. When two or more depolarization treatment methods are used, the order of the treatment methods is not fixed. For example, the heat treatment method can be used for depolarization treatment first, and then the phosphoric acid method can be used for depolarization treatment, or the phosphoric acid method can be used for depolarization treatment first, and then the heat treatment method can be used for depolarization treatment.

[0093] In some embodiments of the present invention, the heat treatment method is to place the electrode foil under oxygen conditions for heat treatment, and the heat treatment temperature can be 400°C to 550°C. The heat treatment temperature provided by the present invention can be a value of an interval composed of any two values ​​in the above range, for example, it can be 400°C to 480°C, or 480°C to 550°C, and so on. The heat treatment temperature provided by the present invention can also be one of 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any value that meets the above range value.

[0094] In some embodiments of the present invention, the heat treatment method places the electrode foil under oxygen conditions for heat treatment, and the heat treatment time can be 1min to 15min. The heat treatment time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 1min to 8min, or 8min to 15min, and so on. The heat treatment time provided by the present invention can also be one of 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min or any value that meets the above range value.

[0095] In some embodiments of the present invention, the phosphoric acid method is to immerse the electrode foil in a solution, and the temperature of the solution is 40°C to 90°C. The temperature of the solution used in the phosphoric acid method provided by the present invention can be a value in the interval composed of any two values ​​in the above range, for example, it can be 40°C to 65°C, or 65°C to 90°C, and so on. The temperature of the solution used in the phosphoric acid method provided by the present invention can also be one of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value that meets the above range.

[0096] In some embodiments of the present invention, the phosphoric acid method is to immerse the electrode foil in a solution for treatment, and the immersion time can be 0.5min to 15min. The immersion time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 0.5min to 8min, or 8min to 15min, and so on. The immersion time provided by the present invention can also be one of 0.5min, 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min or any value that meets the above range value.

[0097] In some embodiments of the present invention, the mass percentage of phosphorus in the solution used in the phosphoric acid method is 0.2% to 15%. The mass percentage of phosphorus in the solution used in the phosphoric acid method provided by the present invention can be a value in the interval composed of any two values ​​in the above interval, such as 0.2% to 5%, or 5% to 15%, and so on. The mass percentage of phosphorus in the solution used in the phosphoric acid method provided by the present invention can also be 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15% or any value that meets the above range.

[0098] In some embodiments of the present invention, the solution used in the phosphoric acid method contains inorganic phosphoric acid and / or organic phosphoric acid.

[0099] In some embodiments of the present invention, the inorganic phosphoric acid used in the phosphoric acid method is selected from one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid and hypophosphorous acid.

[0100] In some embodiments of the present invention, the organic phosphoric acid used in the phosphoric acid method is selected from one or more of trimethylphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and acetylphosphonic acid.

[0101] Complement formation

[0102] In the present invention, after the depolarization treatment, a repair formation is usually required to repair and fill the defects.

[0103] In an embodiment of the present invention, the electrode foil after depolarization treatment is firstly washed with pure water and then placed in a treatment liquid, such as a forming liquid, for a re-forming treatment.

[0104] In the embodiment of the present invention, when two or more depolarization treatment methods are used, the order of the depolarization treatment methods is not fixed. For example, the thermal treatment method can be used for depolarization treatment first, and then the phosphoric acid method can be used for depolarization treatment, or the phosphoric acid method can be used for depolarization treatment first, and then the thermal treatment method can be used for depolarization treatment. On this basis, in the embodiment of the present invention, the supplementary formation is performed after the depolarization treatment, and there are many ways of combining the methods.

[0105] In some embodiments of the present invention, a heat treatment method is first used for depolarization treatment, followed by a formation of the filler, then a phosphoric acid method for depolarization treatment, and finally a formation of the filler.

[0106] In some embodiments of the present invention, a phosphoric acid method is first used for depolarization treatment, followed by a formation repair, and then a heat treatment method is used for depolarization treatment, and finally a formation repair is performed.

[0107] In some embodiments of the present invention, a heat treatment method and a phosphoric acid method are used in sequence for depolarization treatment, and then a supplementary formation is performed.

[0108] In some embodiments of the present invention, the depolarization treatment is performed by a phosphoric acid method and a heat treatment method respectively, and then the formation is performed.

[0109] In some embodiments of the present invention, the treatment solution used for the formation is at least one selected from ammonium adipate solution, boric acid solution, and ammonium dihydrogen phosphate solution.

[0110] In some embodiments of the present invention, the mass percentage of the treatment liquid solute used for the supplementary formation is 0.3% to 20%. The mass percentage of the treatment liquid solute provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.3% to 6%, 6% to 10%, 10% to 20%, and so on. The mass percentage of the treatment liquid solute provided by the present invention can also be 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value that meets the above range value.

[0111] In some embodiments of the present invention, the treatment solution formed is selected from at least one of a 1% by mass ammonium dihydrogen phosphate solution and a 15% by mass ammonium adipate solution.

[0112] In some embodiments of the present invention, the temperature of the supplementary formation may be 65°C to 90°C, for example, the electrode foil is placed in a treatment solution at 65°C to 90°C for supplementary formation. The supplementary formation temperature provided by the present invention may be a value in an interval consisting of any two values ​​in the above interval, for example, it may be 65°C to 75°C, or 75°C to 90°C, and so on. The supplementary formation temperature provided by the present invention may also be one of 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any value that satisfies the above range.

[0113] In some embodiments of the present invention, the time for the complementary formation can be 2min to 20min, that is, the time for the complementary formation is 2min to 20min to reach the constant time of the set complementary formation voltage. The complementary formation time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 2min to 10min, or 10min to 20min, and so on. The complementary formation time provided by the present invention can also be one of 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min or any value that meets the above range value.

[0114] In some embodiments of the present invention, the current density of the fill formation is 10 mA / cm 2 ~100mA / cm 2 The current density provided by the present invention can be a value in the interval formed by any two values ​​in the above interval, for example, it can be 10mA / cm 2 ~50mA / cm 2 , or 50mA / cm 2 ~100mA / cm 2 The current density of the compensation provided by the present invention can also be 10mA / cm 2 , 20mA / cm 2 、30mA / cm 2 , 40mA / cm 2 , 50mA / cm 2 、60mA / cm 2 , 70mA / cm 2 、80mA / cm 2 , 90mA / cm 2 , 100mA / cm 2 or any value that satisfies the above range.

[0115] In some embodiments of the present invention, the complementary forming voltage is 90% to 100% of the highest forming voltage in the forming process. For example, the complementary forming voltage is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% of the highest forming voltage or any value that satisfies the above range.

[0116] Double-sided SiO2 coating

[0117] In the present invention, the electrode foil after the repair is cleaned with pure water and dried, and then SiO2 films are deposited on both sides, so that nano-porous SiO2 with high dielectric properties is introduced into the surface layer of the aluminum oxide film.

[0118] In an embodiment of the present invention, the thickness of the silicon dioxide (SiO2) film is 2nm to 25nm. For example, the thickness of the silicon dioxide film can be one of 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, and 25nm, or any value that satisfies the above range.

[0119] In the embodiment of the present invention, the thickness of the aluminum oxide film can be adjusted according to the specifications of the product and is not particularly limited.

[0120] In some embodiments of the present invention, the silicon dioxide film can be formed by at least one of chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD), and atomic layer deposition (ALD). For example, when PECVD is used, the deposition reaction can be carried out at a lower temperature, the film is amorphous, the film is uniform and dense, has good process repeatability, and can be firmly combined with the aluminum oxide film.

[0121] In some embodiments of the present invention, the deposition reaction gases are SiH4 and N2O, and the flow ratio of SiH4 to N2O is 1:1 to 1:6. For example, the flow ratio of SiH4 to N2O can be one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or any value satisfying the above range.

[0122] In some embodiments of the present invention, the silicon dioxide film may be formed by a method selected from plasma enhanced chemical vapor deposition (PECVD).

[0123] In some embodiments of the present invention, the process parameters of plasma enhanced chemical vapor deposition include a deposition temperature of 150°C to 350°C, for example, the deposition temperature may be one of 150°C, 200°C, 250°C, 300°C, 350°C or any value satisfying the above range; a working pressure of 20Pa to 150Pa, for example, the working pressure may be one of 20Pa, 50Pa, 75Pa, 100Pa, 125Pa, 150Pa or any value satisfying the above range; a RF power of 10W to 200W, for example, the RF power may be one of 10W, 50W, 100W, 150W, 200W or any value satisfying the above range.

[0124] In some embodiments of the present invention, the production direction of the SiO2 film is perpendicular to the surface of the aluminum foil, and there are pores between the SiO2 particles.

[0125] Phosphate treatment

[0126] In the present invention, the electrode foil after the SiO2 film is plated is placed in a phosphorus-containing solution, and the phosphorus element can penetrate into the nanoporous SiO2 film, so that the phosphate radical is connected to the surface of the SiO2 particles through the silanol group (Si-OH), and a hydration-resistant layer similar to phosphorus silicon glass is formed on the outermost layer of the composite oxide film. At the same time, a high-efficiency water-retaining layer with a complex three-dimensional network structure containing silicon, phosphorus and aluminum elements is formed at the interface of the SiO2 film and the Al2O3 film. Figure 1 As shown, the Al atoms on the surface of the aluminum oxide film are inhibited from combining with water to form AlO-H bonds and Al-OH bonds, which greatly reduces the amount of water molecules adsorbed on the surface and inhibits the diffusion of water molecules into the inner layer of the oxide film, thereby eliminating surface active points and improving the hydration resistance of the electrode foil.

[0127] In the embodiment of the present invention, the phosphating treatment uses a phosphorus-containing solution.

[0128] In some embodiments of the present invention, the phosphorus-containing solution includes one or more of inorganic phosphoric acid, inorganic phosphate, organic phosphoric acid and organic phosphate.

[0129] In some embodiments of the present invention, the inorganic phosphoric acid is one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid, and hypophosphorous acid.

[0130] In some embodiments of the present invention, the inorganic phosphate is one or more of orthophosphate, pyrophosphate, tripolyphosphate, metaphosphate, hypophosphate, phosphite, pyrophosphite, metaphosphite and hypophosphite.

[0131] In some embodiments of the present invention, the organic phosphoric acid is one or more of trimethylphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and acetylphosphonic acid.

[0132] In some embodiments of the present invention, the organic phosphate is one or more of trimethylphosphonate, aminotrimethylenephosphonate, ethylenediaminetetramethylenephosphonate, diethylenetriaminepentamethylenephosphonate, acetyl phosphate,

[0133] In some embodiments of the present invention, the phosphorus element in the phosphorus-containing solution exists in the form of one or more phosphate ions selected from monohydrogen phosphate, dihydrogen phosphate, and orthophosphate.

[0134] In some embodiments of the present invention, the mass percentage of phosphorus in the phosphorus-containing solution is 0.08% to 15%. The mass percentage of phosphorus in the phosphorus-containing solution provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.08% to 8%, or 8% to 15%, and so on. The mass percentage of phosphorus in the phosphorus-containing solution provided by the present invention can also be 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value that meets the above range value.

[0135] In some embodiments of the present invention, the phosphorus-containing solution may be at least one of a phosphoric acid solution, a phosphorous acid solution, a phosphate solution, or a phosphite solution.

[0136] In some embodiments of the present invention, the temperature of the phosphating treatment is 40°C to 85°C. The phosphating treatment temperature provided by the present invention can be a value of an interval consisting of any two values ​​in the above range, for example, it can be 40°C to 60°C, or 60°C to 85°C, and so on. The phosphating treatment temperature provided by the present invention can also be one of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, or any value that meets the above range.

[0137] In some embodiments of the present invention, the phosphating time is 0.5 min to 15 min. The phosphating time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 0.5 min to 10 min, or 10 min to 15 min, and so on. The phosphating time provided by the present invention can also be one of 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or any value that meets the above range.

[0138] Annealing

[0139] In the present invention, the electrode foil that has completed the phosphating treatment is subjected to a rapid annealing treatment to improve the internal structure of the SiO2 film, increase the density, and make the SiO2 film firmly bonded to the surface of the Al2O3 film, thereby enhancing the interface fusion of the two. At the same time, the phosphorus element is diffused and distributed more evenly inside the SiO2, and a highly water-resistant network structure similar to phosphorus silicon glass is formed on the surface.

[0140] In an embodiment of the present invention, the temperature of the annealing treatment can be 120°C to 350°C, and an excessively high annealing treatment temperature causes the grain size of the film to become larger, the stress to increase, and then cracks to occur. The annealing treatment temperature provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 120°C to 200°C, or it can be 200°C to 350°C, and so on. The annealing treatment temperature provided by the present invention can also be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or any value that satisfies the above range value.

[0141] In an embodiment of the present invention, the annealing time can be 1min to 20min. The annealing time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 1min to 10min, or 10min to 20min, and so on. The annealing time provided by the present invention can also be one of 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min or any value that meets the above range value.

[0142] The present invention also provides an electrode foil for a low-voltage aluminum electrolytic capacitor. The electrode foil for a low-voltage aluminum electrolytic capacitor is prepared by the above-mentioned preparation method.

[0143] The specific volume of the electrode foil prepared by the present invention is increased. The relative dielectric constant εr of SiO2 is 3.9, and its formation constant K is 0.39nm / V. The relative dielectric constant εr of Al2O3 is 9, and its formation constant K is 1.3nm / V. The εr / K of the SiO2 film is greater than the εr / K of the Al2O3 film, so the specific volume of the electrode foil is increased.

[0144] The present invention also provides an aluminum electrolytic capacitor, which includes the electrode foil for the low-voltage aluminum electrolytic capacitor.

[0145] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0146] Example 1

[0147] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 132Vf low-voltage foil, and the preparation method is as follows:

[0148] S1: Multi-stage electrochemical treatment of corroded foil. Take the corroded low-voltage aluminum foil with a thickness of 105 μm and perform five-stage electrochemical treatment in a 20% ammonium adipate aqueous solution at 85°C. The electrochemical voltages are 21V, 42V, 63V, 84V, and 132V, respectively, and the current density is 100 mA / cm 2 , each constant pressure is maintained for 3 minutes.

[0149] S2: Depolarization treatment and back-forming. The aluminum foil after step S1 was immersed in a phosphoric acid solution with a temperature of 45°C and a phosphorus mass percentage of 2% for 3 minutes; after being washed with pure water, it was placed in a diammonium phosphate aqueous solution with a mass percentage of 2% and a temperature of 85°C for back-forming. The back-forming voltage was 132V, and the constant voltage was maintained for 3 minutes. The current density was 100mA / cm 2 ; Then, heat treatment was performed at 500°C for 2 min, and then the formation was carried out in an aqueous solution of ammonium dihydrogen phosphate with a mass percentage of 2% and a temperature of 85°C. The formation voltage was 132 V, and the constant voltage was maintained for 3 min. The current density was 100 mA / cm 2 .

[0150] S3: Double-sided SiO2 film coating. The aluminum foil that has undergone step S2 is deposited on its surface by PECVD to form a nanoporous SiO2 film. The deposition temperature is 250°C, the deposition reaction gases are SiH4 and N2O, the flow ratio of SiH4 to N2O is 1:2, the SiH4 flow rate is 40sccm, the working pressure is 40Pa, the RF power is 60W, and the SiO2 film deposition thickness is 15nm.

[0151] S4: Phosphating treatment: The aluminum foil after step S3 is immersed in a phosphoric acid solution with a phosphorus content of 0.1% by mass and a temperature of 65° C. for 2 minutes.

[0152] S5: Annealing treatment: The aluminum foil after step S4 is subjected to rapid annealing heat treatment at 350° C. for 2 minutes.

[0153] Example 2

[0154] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 105Vf low-voltage foil, and the preparation method is as follows:

[0155] S1: Multi-stage electrochemical treatment of etched foil. Take the etched low-voltage aluminum foil with a thickness of 105 μm and perform five-stage electrochemical treatment in a 10% ammonium adipate aqueous solution at 70°C. The electrochemical voltages are 21V, 42V, 63V, 84V, and 105V, respectively, and the current density is 60 mA / cm 2 , each constant pressure is maintained for 5 minutes.

[0156] S2: Depolarization treatment and patch formation. The aluminum foil after step S1 is immersed in a phosphoric acid solution with a temperature of 65°C and a phosphorus mass percentage of 2% for 4 minutes; after being washed with pure water, it is heat treated at 480°C for 5 minutes, and then patched in a diammonium phosphate aqueous solution with a mass percentage of 2% and a temperature of 90°C. The patch formation voltage is 105V, and the constant voltage is maintained for 5 minutes. The current density is 20mA / cm 2 .

[0157] S3: Double-sided SiO2 film coating. The aluminum foil that has undergone step S2 is deposited on its surface by PECVD to form a nanoporous SiO2 film. The deposition temperature is 250°C, the deposition reaction gases are SiH4 and N2O, the flow ratio of SiH4 to N2O is 1:1, the SiH4 flow rate is 70sccm, the working pressure is 100Pa, the RF power is 100W, and the SiO2 film deposition thickness is 10nm.

[0158] S4: Phosphating treatment: The aluminum foil after step S3 is immersed in an aminotri(methylenephosphonic) acid solution with a phosphorus content of 5% by mass and a temperature of 45° C. for 10 minutes.

[0159] S5: Annealing treatment: The aluminum foil after step S4 is subjected to rapid annealing heat treatment at 300° C. for 15 minutes.

[0160] Example 3

[0161] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 85Vf low-voltage foil, and the preparation method is as follows:

[0162] S1: Multi-stage electrochemical treatment of etched foil. Take the etched low-voltage aluminum foil with a thickness of 105 μm and perform five-stage electrochemical treatment in a 15% ammonium adipate aqueous solution at 85°C. The electrochemical voltages are 10V, 20V, 30V, 40V, and 85V, respectively, and the current density is 50 mA / cm 2 , each constant pressure is maintained for 10 min.

[0163] S2: Depolarization treatment and patch formation. The aluminum foil after step S1 was heat treated at 550℃ for 2min, then immersed in a phosphorous acid solution with a temperature of 40℃ and a phosphorus mass percentage of 3% for 15min; after being washed with pure water, it was placed in a mixed aqueous solution of boric acid and ammonium dihydrogen phosphate with a mass percentage of 5% and 2% respectively and a temperature of 85℃ for patch formation. The patch formation voltage was 80V, the constant voltage was maintained for 10min, and the current density was 50mA / cm 2 ; Then, heat treatment was performed at 500°C for 2 min, and then the formation was performed in an aqueous solution of ammonium dihydrogen phosphate with a mass percentage of 2% and a temperature of 80°C. The formation voltage was 82 V, and the constant voltage was maintained for 10 min. The current density was 50 mA / cm 2 .

[0164] S3: Double-sided SiO2 film coating. The aluminum foil that has undergone step S2 is deposited on its surface by PECVD to form a nanoporous SiO2 film. The deposition temperature is 250°C, the deposition reaction gases are SiH4 and N2O, the flow ratio of SiH4 to N2O is 1:6, the SiH4 flow rate is 20sccm, the working pressure is 60Pa, the RF power is 50W, and the SiO2 film deposition thickness is 5nm.

[0165] S4: Phosphating treatment: The aluminum foil after step S3 is immersed in a mixed solution of ammonium dihydrogen phosphate and phosphoric acid at a temperature of 75° C. and a phosphorus content of 2.5% by mass for 5 minutes.

[0166] S5: Annealing treatment: The aluminum foil after step S4 is subjected to rapid annealing heat treatment at 280° C. for 10 minutes.

[0167] Example 4

[0168] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 51Vf low-voltage foil, and the preparation method is as follows:

[0169] S1: Multi-stage electrochemical treatment of corroded foil. Take the corroded low-voltage aluminum foil with a thickness of 105 μm and perform five-stage electrochemical treatment in a 15% ammonium adipate aqueous solution at 75°C. The electrochemical voltages are 10V, 20V, 30V, 40V, and 51V respectively, and the current density is 10 mA / cm 2, each constant pressure is maintained for 5 minutes.

[0170] S2: Depolarization treatment and patch formation. The aluminum foil after step S1 was immersed in a phosphoric acid solution with a temperature of 75°C and a phosphorus mass percentage of 10% for 1 minute; after being washed with pure water, it was placed in a mixed aqueous solution of ammonium adipate and diammonium phosphate with a mass percentage of 10% and 0.3% respectively and a temperature of 85°C for patch formation. The patch formation voltage was 51V, the constant voltage was maintained for 5 minutes, and the current density was 100mA / cm 2 ; Then, heat treatment was performed at 500°C for 2 min, and then the formation was performed in aqueous solutions of ammonium adipate and ammonium dihydrogen phosphate with a mass percentage of 10% and 0.3% respectively at a temperature of 85°C. The formation voltage was 51 V, the constant voltage was maintained for 5 min, and the current density was 20 mA / cm 2 .

[0171] S3: Double-sided SiO2 film coating. The aluminum foil that has undergone step S2 is deposited on its surface by PECVD to form a nanoporous SiO2 film. The deposition temperature is 300°C, the deposition reaction gases are SiH4 and N2O, the flow ratio of SiH4 to N2O is 1:5, the SiH4 flow rate is 40sccm, the working pressure is 30Pa, the RF power is 35W, and the SiO2 film deposition thickness is 4nm.

[0172] S4: Phosphating treatment: The aluminum foil after step S3 is immersed in a phosphorous acid solution with a phosphorus content of 5% by mass and a temperature of 40° C. for 10 minutes.

[0173] S5: Annealing treatment: The aluminum foil after step S4 is subjected to rapid annealing heat treatment at 150° C. for 2 minutes.

[0174] Comparative Example 1

[0175] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 132Vf low-voltage foil, and the preparation method is as follows:

[0176] Steps S1 and S2 are the same as those in Example 1.

[0177] S3: The aluminum foil after step S2 is cleaned in pure water and then dried at 90°C.

[0178] Comparative Example 2

[0179] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 132Vf low-voltage foil, and the preparation method is as follows:

[0180] Steps S1, S2 and S3 are the same as those in Example 1.

[0181] S4: Annealing treatment: The aluminum foil after step S3 is subjected to rapid annealing heat treatment at 350° C. for 2 minutes.

[0182] Comparative Example 3

[0183] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 51Vf low-voltage foil, and the preparation method is as follows:

[0184] S1 and S2 are the same as steps in Example 4.

[0185] S3: The aluminum foil after step S2 is cleaned in pure water and then dried at 90°C.

[0186] Comparative Example 4

[0187] A method for preparing an electrode foil for a low-voltage aluminum electrolytic capacitor, wherein the electrode foil is a 51Vf low-voltage foil, and the preparation method is as follows:

[0188] Steps S1, S2 and S3 are the same as those in Example 4.

[0189] S4: Annealing treatment: The aluminum foil after step S3 is subjected to rapid annealing heat treatment at 150° C. for 2 minutes.

[0190] Performance Testing

[0191] According to SJT 11140-2022 test standard for electrode foil for aluminum electrolytic capacitors, the specific capacitance of the electrode foil and the voltage rise time Tr60 after boiling in water for 1 hour were tested.

[0192] At the same time, in order to compare the corrosion resistance of each low-voltage foil, the corrosion resistance evaluation method is specified: after the electrode foil is tested for its withstand voltage value, it is immersed in a 0.3% sulfuric acid solution at 60°C for 3 minutes, and then taken out and rinsed with pure water and its pressure rise time Ts is tested. The test results are detailed in Table 1.

[0193] Table 1 Summary of performance test results of electrode foils prepared in Examples and Comparative Examples

[0194]

[0195] Combined with the data in Table 1, it can be seen that in the preparation method of the low-voltage chemical foil of the present invention, a silicon dioxide film is deposited on the surface of the aluminum oxide film and then subjected to a phosphating treatment and an annealing treatment, and an aluminum oxide-silicon dioxide double-layer composite oxide film is formed on the surface of the low-voltage electrode foil, thereby improving the specific volume. At the same time, the reduction of Tr60 indicates that the hydration resistance is enhanced, and the reduction of Ts indicates that the corrosion resistance is significantly improved.

[0196] In addition, through comparison, it was found that if only the step of depositing the silicon dioxide film is added without subsequent phosphating treatment, the hydration resistance and corrosion resistance of the aluminum foil cannot be improved, which shows that the subsequent phosphating treatment step is also indispensable.

[0197] The preparation method of the present invention can improve the capacity of the low-voltage chemically formed foil, and simultaneously improve the hydration resistance and corrosion resistance, indicating that the overall performance of the low-voltage electrode foil is improved with significant effects.

[0198] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing an electrode foil, characterized in that: The preparation method comprises the following steps: The etched foil is subjected to a chemical treatment to form an aluminum oxide film on the surface thereof; forming a nanoporous silicon dioxide film on the surface of the aluminum oxide film to obtain an electrode foil having an aluminum oxide-silicon dioxide double-layer composite oxide film; and The electrode foil is sequentially subjected to phosphating treatment and annealing treatment.

2. The preparation method according to claim 1, characterized in that The silicon dioxide film has a thickness of 2 nm to 25 nm; Preferably, the silicon dioxide film is formed by one or more methods selected from chemical vapor deposition, physical vapor deposition, plasma enhanced chemical vapor deposition and atomic layer deposition; Preferably, the deposition reaction gases are SiH4 and N2O, and the flow ratio of SiH4 to N2O is 1:1 to 1:

6.

3. The preparation method according to claim 1, characterized in that: The phosphating treatment uses a phosphorus-containing solution; Preferably, the mass percentage of phosphorus in the phosphorus-containing solution is 0.08% to 15%; Preferably, the phosphorus-containing solution comprises one or more of inorganic phosphoric acid, inorganic phosphate, organic phosphoric acid and organic phosphate; Preferably, the inorganic phosphoric acid is one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid and hypophosphorous acid; Preferably, the inorganic phosphate is one or more of orthophosphate, pyrophosphate, tripolyphosphate, metaphosphate, hypophosphate, phosphite, pyrophosphate, metaphosphite and hypophosphite; Preferably, the organic phosphoric acid is one or more of trimethylphosphonic acid, aminotrimethylenephosphonic acid, ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid and acetylphosphonic acid; Preferably, the organic phosphate is one or more of trimethylphosphonate, aminotrimethylenephosphonate, ethylenediaminetetramethylenephosphonate, diethylenetriaminepentamethylenephosphonate, and acetylphosphate.

4. The preparation method according to claim 1 or 3, characterized in that: The temperature of the phosphating treatment is 40°C to 85°C; Preferably, the phosphating treatment time is 0.5 min to 15 min.

5. The preparation method according to claim 1, characterized in that: The annealing temperature is 120°C to 350°C; Preferably, the annealing treatment time is 1 min to 20 min.

6. The preparation method according to claim 1, characterized in that: The chemical formation treatment includes one to six stages of chemical formation, and the chemical formation liquid used in each stage of chemical formation is independently selected from one or more of ammonium adipate solution, boric acid solution and diammonium dihydrogen phosphate solution; Preferably, the formation temperature of each stage of formation is independently 65°C to 90°C, and the formation time of each stage of formation is independently 2min to 20min; Preferably, the current density of each stage is independently 10 mA / cm 2 ~100mA / cm 2 ; Preferably, in each stage of formation, the formation voltage increases step by step from the first stage to the last stage; Preferably, the mass percentage of the formation liquid used in each stage of formation is independently 0.3% to 20%.

7. The preparation method according to claim 1, characterized in that: The preparation method further comprises performing at least one depolarization treatment after the chemical formation treatment and before forming the nanoporous silicon dioxide film; Preferably, the depolarization treatment is selected from one or more of a heat treatment method and a phosphoric acid method; Preferably, the temperature of the heat treatment method is 400°C to 550°C, and the time of the heat treatment method is 1min to 15min; Preferably, the temperature of the phosphoric acid method is 40°C to 90°C, and the time of the phosphoric acid method is 0.5min to 15min; Preferably, the mass percentage of phosphorus in the solution used in the phosphoric acid method is 0.2% to 15%; Preferably, the solution used in the phosphoric acid method contains inorganic phosphoric acid and / or organic phosphoric acid; Preferably, the inorganic phosphoric acid used in the phosphoric acid method is selected from one or more of orthophosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, metaphosphoric acid, hypophosphoric acid, phosphorous acid, pyrophosphorous acid, metaphosphorous acid and hypophosphorous acid; Preferably, the organic phosphoric acid used in the phosphoric acid method is selected from one or more of trimethylphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and acetylphosphonic acid.

8. The preparation method according to claim 7, characterized in that: The preparation method further comprises performing at least one supplementary formation after the depolarization treatment and before forming the nanoporous silicon dioxide film; Preferably, the temperature of the patch formation is 65°C to 90°C, and the time of the patch formation is 2min to 20min; Preferably, the current density of the patch formation is 10 mA / cm 2 ~100mA / cm 2 ; Preferably, the voltage of the complementary formation is 90% to 100% of the highest formation voltage of the formation treatment; Preferably, the treatment solution used in the formation of the patch is selected from one or more of ammonium adipate solution, boric acid solution and diammonium dihydrogen phosphate solution; Preferably, the mass percentage of the solute in the treatment solution used for the replenishment formation is 0.3% to 20%.

9. An electrode foil, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. An aluminum electrolytic capacitor, characterized in that: The invention comprises an electrode foil prepared by the preparation method according to any one of claims 1 to 8 or an electrode foil according to claim 9.

Citation Information

Cited By

  • Electrode foil, preparation method thereof and aluminum electrolytic capacitor

    CN121096788A